Genetic and environmental contributions to psychopathological symptoms stability and change across the COVID-19 pandemic. (August 2022) - Gigantesco, Antonella; Fagnani, Corrado; Picardi, Angelo; Stazi, Maria Antonietta; Medda, Emanuela
Highlights: Longitudinal twin study of anxiety, depression and stress during COVID-19 pandemic. Moderate stability of examined psychopathological symptoms over a 6-month period. Genetic factors mainly responsible for the stability of psychopathological symptoms. Different unique environmental factors involved in the two study waves. Abstract: Several longitudinal studies investigated changes in mental health related to the pandemic event. However, little research has focused on the mediating role of environmental and genetic factors. The current prospective study aimed to evaluate the genetic and environmental contributions to the stability of symptoms of depression, anxiety and stress during the COVID-19 crisis. A total of 798 adult twins, previously enrolled in the Italian Twin Register, participated in the study and completed on-line questionnaires sent out on June 2020 and December 2020. The nine-item Patient Health Questionnaire (PHQ-9), the six-item State-Trait Anxiety Inventory (STAI-6), and the Impact of Event Scale - Revised (IES-R) were administered to assess depressive and anxiety symptoms, and pandemic-related subjective distress, respectively. A considerable longitudinal stability was observed for each trait (range: 0.57, STAI-6 - 0.67, PHQ-9). Bivariate Cholesky decomposition indicated that genetic factors explained from 53% (IES-R) to 61% (STAI-6) of between-wave covariance and that genetic overlap between the two waves was almost complete (range: 0.91, STAI-6 – 0.99, PHQ-9). Our findings support the hypothesis, at least over the 6-month period examined, of a genetic stability between waves and of an environmental discontinuity due to changes in life conditions during the pandemic.